A tomato receptor-like cytoplasmic kinase, SlZRK1, acts as a negative regulator in wound-induced jasmonic acid accumulation and insect resistance. (26th July 2021) - Sun, Zongyan; Zang, Yudi; Zhou, Leilei; Song, Yanping; Chen, Di; Zhang, Qiaoli; Liu, Chengxia; Yi, Yuetong; Zhu, Benzhong; Fu, Daqi; Zhu, Hongliang; Qu, Guiqin
Abstract : Tomato receptor-like cytoplasmic kinase SlZRK1 may act as a pseudokinase and negatively regulate wound-induced jasmonic acid response and plant resistance to herbivorous insects. Abstract: Jasmonates accumulate rapidly and act as key regulators in response to mechanical wounding, but few studies have linked receptor-like cytoplasmic kinases (RLCKs) to wound-induced jasmonic acid (JA) signaling cascades. Here, we identified a novel wounding-induced RLCK-XII-2 subfamily member (SlZRK1) in tomato ( Solanum lycopersicum ) that was closely related to Arabidopsis HOPZ-ETI-DEFICIENT 1 (ZED1)-related kinases 1 based on phylogenetic analysis. SlZRK1 was targeted to the plasma membrane of tobacco mesophyll protoplasts as determined by transient co-expression with the plasma membrane marker mCherry–H + -ATPase. Catalytic residue sequence analysis and an in vitro kinase assay indicated that SlZRK1 may act as a pseudokinase. To further analyse the function of SlZRK1, we developed two stable knock-out mutants by CRISPR/Cas9. Loss of SlZRK1 significantly altered the expression of genes involved in JA biosynthesis, salicylic acid biosynthesis, and ethylene response. Furthermore, after mechanical wounding treatment, slzrk1 mutants increased transcription of early wound-inducible genes involved in JA biosynthesis and signaling. In addition, JA accumulation after wounding and plant resistance to herbivorous insects also were enhanced. Our findings expand plant regulatory networks in the wound-induced JA production by adding RLCKs as a new component in the wound signal transduction pathway.